2017
DOI: 10.3389/fpsyg.2017.00560
|View full text |Cite
|
Sign up to set email alerts
|

Childbirth Induced Posttraumatic Stress Syndrome: A Systematic Review of Prevalence and Risk Factors

Abstract: Background: Posttraumatic stress related with the childbirth experience of full-term delivery with health outcomes has been recently documented in a growing body of studies. The magnitude of this condition and the factors that might put a woman at risk for developing childbirth-related postpartum posttraumatic stress disorder (PP-PTSD) symptoms are not fully understood.Methods: In this systematic review of 36 articles representing quantitative studies of primarily community samples, we set to examine PP-PTSD p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
181
1
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(240 citation statements)
references
References 61 publications
18
181
1
7
Order By: Relevance
“…Similar to the present study, other studies also reported the significant relation between delivery experiences and PTSD following childbirth [18,19]. In the study conducted by Dekel et al [20], negative experience of delivery was considered as the most important predictor of PTSD following childbirth. In the study of Hollander et al [19] emotional and practical support by the medical team during labor was associated with decreased possibility of PTSD following childbirth and according to Simpson et al [21], low quality of the caregivers interactions during labor was reported as one of the most important risk factors for experiencing traumatic birth.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to the present study, other studies also reported the significant relation between delivery experiences and PTSD following childbirth [18,19]. In the study conducted by Dekel et al [20], negative experience of delivery was considered as the most important predictor of PTSD following childbirth. In the study of Hollander et al [19] emotional and practical support by the medical team during labor was associated with decreased possibility of PTSD following childbirth and according to Simpson et al [21], low quality of the caregivers interactions during labor was reported as one of the most important risk factors for experiencing traumatic birth.…”
Section: Discussionsupporting
confidence: 88%
“…Body image dissatisfaction also has consequences for women's mental health and has been positively correlated with perinatal depression symptoms across multiple studies . Another concern during this period is postpartum posttraumatic stress disorder, estimated to occur in 4% to 16% of women after childbirth . In a small feasibility study, an 8‐week mindfulness‐based class series reduced symptoms of posttraumatic stress, depression, and shame in adult survivors of trauma .…”
Section: Discussionmentioning
confidence: 99%
“…34 Another concern during this period is postpartum posttraumatic stress disorder, estimated to occur in 4% to 16% of women after childbirth. 9 In a small feasibility study, an 8-week mindfulness-based class series reduced symptoms of posttraumatic stress, depression, and shame in adult survivors of trauma. 35 Although it may not be feasible to offer mindfulness classes specifically for women who experienced traumatic childbirth, incorporating a trauma-informed perspective into mindfulness classes may benefit women survivors of trauma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mental health issues can easily ariseduring the early postpartum period [40,49,50]; although the majority of women coped well. Nevertheless, for some childbirthwas a stressful experience, with the increased potential for developing postpartum post-traumatic stress disorder symptoms [51].Literature reveals that the prevalence of postnatal depression is highest among migrant women [52]. Brief midwife-led counselling interventions for women who report distressing birth experiences have been found to be effective for reducing symptoms of trauma, depression, stress, and coping with feelings of self-blame [53].…”
Section: Need For Responsive and Competentstaff In The Maternity Carementioning
confidence: 99%